Crafting Standardization: A Framework for Environmental Degradation Damages At The ICJ. - Lauren Maunder (Washington University Global Studies Law Review, 2025)
In recent decades, international environmental law has emerged as a distinct field of legal work and academic study. As the impacts of human-generated environmental destruction, waste, and other byproducts of industrial development are increasingly perceived in a negative light, some states have begun to acknowledge their “responsibility to ensure that activities within their own jurisdiction or control do not cause damage to the environment of other States." ...[T]he goal of this note is to forge a path toward greater clarity in environment-focused ICJ decisions. Examining the Court’s decision in Costa Rica v. Nicaragua, it becomes evident that creating a standardized framework for calculating environmental damages in contentious cases may assist the Court in achieving that clarity.
Keywords: Environmental Degradation; ICJ; Damages; Environment; International Responsibility; environmental law